2020
DOI: 10.1016/j.rmcr.2020.101168
|View full text |Cite
|
Sign up to set email alerts
|

Short-course modified regimen intrapleural alteplase and pulmozyme (DNase) in pleural infection

Abstract: Pleural infection is a common clinical condition leading to hospitalisation. In the last decade, advances in pleural research have led to a paradigm shift in the treatment of complex effusion from a surgical approach to a less invasive non-surgical approach using a combination of intrapleural fibrinolytics and pulmozyme (DNase). We report 3 patients with pleural infection. Intercostal chest catheter failed to drain the complex effusion. They were subsequently treated with a modified short-course regimen of alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…Few studies reported on the use of intrapleural urokinase or streptokinase in tuberculous effusion to facilitate pleural fluid drainage and the occurrence of residual pleural thickening [8,11,12]. There is limited literature on the use of intrapleural alteplase (with supplementary DNase) in complex tuberculous pleurisy [13,14]. Our cases showed that intrapleural alteplase and DNase facilitated more infected fluid drainage with clinical resolution of fever and dyspnoea.…”
Section: Discussionmentioning
confidence: 77%
“…Few studies reported on the use of intrapleural urokinase or streptokinase in tuberculous effusion to facilitate pleural fluid drainage and the occurrence of residual pleural thickening [8,11,12]. There is limited literature on the use of intrapleural alteplase (with supplementary DNase) in complex tuberculous pleurisy [13,14]. Our cases showed that intrapleural alteplase and DNase facilitated more infected fluid drainage with clinical resolution of fever and dyspnoea.…”
Section: Discussionmentioning
confidence: 77%
“…é reservada para pacientes com baixo risco cirúrgico, além de ser uma opção inacessível e onerosa para a grande maioria da população brasileira. (2,4) Embora bem estabelecido para o manejo do derrame pleural infectado (parapneumônico), (3)(4)(5)(6)(7) poucos estudos avaliaram a eficácia da terapia intrapleural para pacientes com diagnóstico de ET, seja com fibrinólise isoladamente ou em associação com DNase, limitados a poucas séries de casos. (5) Aqui, relatamos o caso de um paciente diagnosticado com ET com sintomas persistentes e derrame pleural, apesar do Tratamento Diretamente Observado (TDO).…”
Section: Carta Ao Editorunclassified
“…No entanto, a terapia intrapleural adjuvante com alteplase e DNase por 3 dias resultou em melhora clínica, laboratorial e radiológica, associada a uma curta permanência hospitalar, sem necessidade de procedimentos cirúrgicos mais invasivos e sem efeitos adversos Não há consenso sobre a dose intrapleural a ser utilizada. (3,6) Portanto, estudos maiores precisam ser realizados para avaliar a eficácia e segurança do uso intrapleural da alteplase-DNase em ET como terapia alternativa às intervenções cirúrgicas.…”
Section: Carta Ao Editorunclassified